DETERMINANTS OF THE ORGANIZATIONAL PERFORMANCE OF BUSINESSES IN NINH THUAN PROVINCE - Tuyet, Mai Thi Anh; Phong, Vo Tan; Do Van Ly (PEOPLE: International Journal of Social Sciences, 2024)
This research explores the critical factors influencing organizational performance in businesses based in Ninh Thuan Province, Vietnam. Leveraging key theoretical frameworks, including Resource-Based View and Dynamic Capability Theory, the study evaluates the impacts of human resource management practices, organizational culture, organizational innovation, intellectual capital, and organizational citizenship behavior (OCB). Using Structural Equation Modeling, data from 412 senior and middle-level managers were analyzed to validate the proposed hypotheses. The findings highlight that organizational culture exerts the most significant influence on performance, followed closely by OCB, intellectual capital, HRM practices, and organizational innovation. These results underscore the interplay between these factors, emphasizing the need for a robust organizational culture, strategic HRM, and proactive engagement in intellectual capital development. The study provides a comprehensive foundation for managerial strategies aimed at improving organizational efficiency, fostering innovation, and ensuring sustainable growth in competitive markets.